FAKTOR PENGHAMBAT MEMBACA PERMULAAN PADA SISWA KELAS II SDN 32 CAKRANEGARA TAHUN AJARAN 2020/2021 - Sri Ayu Merlinda Yani; Khairun Nisa; Heri Setiawan (Program Studi PGSD, FKIP, Universitas Mataram, 2021)
This study aims to determine the inhibiting factors for early reading in grade II students of SDN 32 Cakranegara and alternative solutions that can be used so that they do not experience obstacles in beginning reading. Internal factors include intelligence, interests, talents, and motivation, while external factors include family environment, school environment, and community environment. This type of research uses a descriptive qualitative approach. Data collection techniques were carried out through interviews, observation, and documentation. The data analysis technique used is data reduction, data presentation, conclusion or verification. . Test the validity of the data using triangulation of sources, and the availability of references. The subjects of this study were second grade students. The results of this study indicate that the inhibiting factor for early reading of students in grade II is the lack of interest, talent, motivation from within the students themselves to learn to read, this is also supported by family and school environmental factors. First, the lack of support and motivation from parents and families towards students in the absence of special attention given to students in teaching students to read at home, secondly, the absence of teacher creativity in teaching students to read and the absence of facilities from schools that support the learning process. There are also strategic efforts used by the teacher in overcoming the obstacles to students' early reading, namely dividing students / focusing on teaching students who cannot read, providing special books for early reading, playing games / games, reminding parents to often teach children to read at home, no matter how busy they are, and train students on a daily basis. Keywords: analysis, inhibiting factors, early reading, SDN 32 Cakranegara.